False witness : a novel - Margolin, Phillip (Minotaur Books, 2025)
"A lawyer who was set-up, imprisoned, and disbarred, only to be vindicated and reinstated, is determined to find out who set her up and cover their tracks with a trail of dead bodies Defense Attorney Karen Wyatt exposed corruption in the police force and the District Attorney's office while getting her client exonerated in court. But in doing so, she put a target on her back and she was set-up on fake drug charge, imprisoned and disbarred until the conspiracy unraveled and her innocence was proven. Now reinstated to the bar, Wyatt is still interested in finding out who ordered her to be set-up - but the key figures were either killed or are in Witness Protection. In the meantime, Wyatt is a practicing defense attorney, whose current client is either guilty of a heinous murder, or is a too-trusting patsy for an acquaintance set-up for a crime he didn't commit. It will take all of Wyatt's genius to defend her client successfully but that's just one piece of an increasingly complex puzzle. With a deadly criminal drug gang, a powerful, corrupt figure hiding in the D.A.'s office, and a Congressman who turned up with an unbelievable story after disappearing for days, False Witness is twisty, breathtaking, and unpredictable thriller"-- Provided by publisher.